Study on security architecture in the Internet of Things - Lan Li (2012 International Conference on Measurement, Information and Control, 2012)
The future Internet of Things as an intelligent collaboration of miniaturized sensors poses new challenges to security and end-user privacy, the security in the lOT is one of the core technologies that will influence the security and sustainable development of the lOT. Therefore, a well-defined security architecture and security system for the lOT will have great impact on the save application and sustainable development of the This paper tends to analyze the security requirements in different layers of the lOT, and hence establish a security architecture system for the expecting to offer a theoretical reference for the establishment of reliable security systems of information for the in the future.